Synovial osteochondromatosis - Devnani, Anand Sobhraj (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2007)
We report three patients with synovial osteochondromatosis to highlight that simple removal of loose bodies and limited synovectomy gives symptomatic relief and has low risk of recurrence in the short term.